Determinants of climate change adaptation strategies and intensity of use; micro level evidence from crop farmers in Kenya - Ndiwa, Aurillia Manjella; Mburu, John; Mulwa, Richard; Chumo, Chepchumba (Frontiers in Sustainable Food Systems, 2024)
Climate change and its negative impacts pose a threat to crop production in Kenya. However, climate change adaptation strategies have the potential to address the challenges faced by crop farmers. Despite this, there is limited literature to inform policy on the best interventions to help farmers deal with climate issues. This study assessed the determinants of climate change adaptation strategies and the intensity of their use among 723 crop farmers in Busia County, Kenya, selected through a multistage sampling technique. Data was collected using a structured questionnaire and analyzed using Principal Component Analysis (PCA), Multinomial Logit Regression, and the Ordered Probit Model. The climate change adaptation strategies were categorized into four: crop diversity, cover crops, use of drought resistance crops and irrigation. According to the results, the factors that contributed to the uptake of the different adaptation strategies were age, household size, access to credit, training access, off-farm income, group membership, frequency of receiving climate change information and extension services. While the major factors that influence the uptake of multiple climate change adaptation strategies was access to credit and off-farm income. The study shows that certain adaptation strategies, such as use of cover crops, do not require credit and offer an important option in an environmental with limited resources. On the other hand, adaptation measures like irrigation demand financial resources for farmers to implement them. This shows the importance of information and awareness in the adoption of adaptation strategies, as well as the supportive role of financial resources, particularly for adopting multiple strategies. The study therefore suggests implementing policies and interventions that encompass both knowledge-based strategies such as extension services, training, climate change education, and group participation as well as financial mechanisms like income generation activities and access to credit. These integrated strategies will enable farmers to adopt various climate change adaptation methods for sustainable crop production.